Searches for Population III pair-instability supernovae: Impact of gravitational lensing magnification. (15th April 2019) - Wong, Kenneth C; Moriya, Takashi J; Oguri, Masamune; Hilbert, Stefan; Koyama, Yusei; Nomoto, Ken'ichi
Abstract: Superluminous supernovae have been proposed to arise from Population III progenitors that explode as pair-instability supernovae (PISNe). Population III stars are the first generation of stars in the Universe, and are thought to have formed as late as z ∼ 6. Future near-infrared imaging facilities such as ULTIMATE-Subaru will potentially be able to detect and identify these PISNe with a dedicated survey. Gravitational lensing by intervening structure in the Universe can aid in the detection of these rare objects by magnifying the high- z source population into detectability. We perform a mock survey with ULTIMATE-Subaru, taking into account lensing by line-of-sight (LOS) structure to evaluate its impact on the predicted detection rate. We compare a LOS mass reconstruction using observational data from the Hyper Suprime Cam survey to results from cosmological simulations to test their consistency in calculating the magnification distribution in the Universe to high z, but find that the data-based method is still limited by an inability to accurately characterize structure beyond z ∼ 1.2. We also evaluate a survey strategy of targeting massive galaxy clusters to take advantage of their large areas of high magnification. We find that targeting clusters can result in a gain of a factor of about two in the predicted number of detected PISNe at z > 5, and even higher gains with increasing redshift, given our assumed survey parameters. For the highest-redshift sources at z ∼ 7–9, blank field surveys will not detect any sources, and lensing magnification by massive clusters will be necessary to observe this population.